2006
DOI: 10.1111/j.1398-9995.2006.00978.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of neuromuscular blocking agent hypersensitivity reactions using cytofluorimetric analysis of basophils

Abstract: Basotest may be useful for the diagnosis of NMBA allergy in patients with a suspicion of recent IgE-mediated hypersensitivity reaction to NMBA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(82 citation statements)
references
References 24 publications
2
77
0
3
Order By: Relevance
“…ST should be done within 4-6 weeks after the reaction and their sensitivity decreases over time; this decrease is faster for betalactams than for NMBAs (grade of recommendation, D) [114,115].…”
Section: Skin Testsmentioning
confidence: 99%
“…ST should be done within 4-6 weeks after the reaction and their sensitivity decreases over time; this decrease is faster for betalactams than for NMBAs (grade of recommendation, D) [114,115].…”
Section: Skin Testsmentioning
confidence: 99%
“…Evidence has accumulated that flow cytometric analysis and quantification of in vitro activated basophils can add to the diagnosis of anaphylaxis from NMBA (64)(65)(66)(67). In these series, sensitivity and specificity of the technique is around 60 and 90% respectively.…”
Section: Neuromuscular Blocking Agentsmentioning
confidence: 99%
“…This sensitivity is lower (36%) when the marker CD203c is used (Sudheer et al, 2005). However, results are discordant; Kvedarine et al (Kvedariene et al, 2006) observed in 47 patients a sensitivity of 36% and a specificity of 93% performing BAT (CD63 in whole blood). On the other hand, Ebo et al (Ebo et al, 2006b) reported the sensitivity of a similar BAT technique to be 91.7% and the specificity 100% for rocuronium in a study including 14 patients with an anaphylactic reaction to drugs and with a positive skin test to rocuronium.…”
Section: Basophil Activation Test In Muscle Relaxant Allergic Reactionsmentioning
confidence: 99%
“…Relevant studies have found that BAT sensitivity and specificity for muscle relaxants varied from 36% to 92% and 93% to 100%, respectively (Sudheer et al, 2005). Most of these studies reported a high specificity and a sensitivity above 50%, reaching 91% (Abuaf et al, 1999;Kvedariene et al, 2006;Laxenaire et al, 1999;Monneret et al, 2002;Moss, 1995;Stellato et al, 1991). This sensitivity is lower (36%) when the marker CD203c is used (Sudheer et al, 2005).…”
Section: Basophil Activation Test In Muscle Relaxant Allergic Reactionsmentioning
confidence: 99%
See 1 more Smart Citation